Exploring the Demand for Retirement Planning Advice: The Role of Financial Literacy - Seay, Martin C.; Kim, Kyoung Tae; Heckman, Stuart J. (My University, 2018)
This research extends previous literature on the relationship between financial literacy and financial advice seeking in three ways: (1) we examine financial planner use specifically within the context of retirement planning, (2) we incorporate Huston’s (2010) framework of financial literacy, and (3) we use longitudinal data to investigate the initiation, maintenance, and termination of financial planner use. Results from the 2010 and 2012 National Longitudinal Survey of Youth 1979 (NLSY79) show a positive association between the components of financial literacy and financial planner use for retirement planning.
Keywords: Retirement planning; Financial planner use; Financial advice